The estimation of pollen viability of snowdrop (Galanthus nivalis L.) - Kovács, G. (International Journal of Horticultural Science, 2000)
In the present experiment pollen viability of snowdrop were tested using four vital dyes (TTC, Baker' procedure, MTT and FDA) to determine their potential to differentiate fresh living pollen from pollen heated for 12 hours at 80 °C (killed pollen). We found that two of the four dyes previously employed to determine viability also stained killed pollen in the case of snowdrop, while the FDA and MIT did not. We suggest that the two latter are probably the best method to test snowdrop pollen viability, since they do not normally stain either killed or aborted pollen.